Worldwide Efficiency of Bioremediation Techniques for Organic Pollutants in Soil: A Brief Review - Sana Akhtar; Ayesha Mohsin; Aiman Riaz; Farhan Mohsin (Geosfera Indonesia, 2023)
Soil pollution is a major human and environmental issue. Among the several components of soil degradation, organic contaminant in soil is regarded as a significant factor that causes considerable damage to the environment along with several health dangers to humans. Polychlorinated biphenyls, polycyclic aromatic hydrocarbons, polychlorinated dibenzofurans, poly-brominated biphenyls, organic fuels particularly gasoline and diesel, herbicides, insecticides (carbamate and organophosphorus) are by far the most common forms of organic pollutants identified in soils. The employment of living organisms such as microorganisms and plants in bioremediation technology reduces/degrades, eliminates, and transforms pollutants found in soils, sediments, and water. This review examine and critically view the efficiency of bioremediation techniques for the polluted sites. The most common bioremediation technologies for the treatment of organic pollutants are bioventing, bio-sparging, bio-slurping, bio-augmentation, phytoremediation, bio-immobilization, bio-sorption, composting, land farming, aerobic degradation, co-metabolic and natural attenuation. The efficiency of these techniques depends on the pH, type of soil, level of oxygen, any other electron acceptors, temperature, and the nutrients. Selection of the treatment process depends upon the type of pollutant, concentration of the contaminant, site and source of pollution. All the treatment techniques are not good for all type of pollutants. Cost-effective techniques are mostly used worldwide as they have more public acceptance. Pump and treat methods were mostly used in Past but due to its non-reliability and excessive cost, these techniques are no longer in use.